Climate variability regulates population dynamics of a threatened freshwater fish - Tonkin, Z; Sharley, J; Fanson, B; Raymond, S; Ayres, R; Lyon, J; Balcombe, S; Bond, N (Endangered species research, 2019)
Most predictions for the future climate in temperate ecosystems show longer periods of drought followed by more extreme precipitation events. These changes in flow regimes can strongly affect riverine fish populations; therefore, assessing the recovery of populations following these episodic events provides important information to help guide species management. This study investigated the dynamics of 5 spatially distinct riverine populations of the nationally endangered Macquarie perch Macquaria australasica in southeastern Australia from 2007-2018, a period that included the tail end of a decadal long drought followed by extreme fluctuations in river flow. Modelling catch rates and size trends, we found that 4 of the 5 populations showed some synchrony and underwent a slow recovery that was undetectable for several years. The largest increases in population size were driven by the survival of new recruits. Despite this general trend, we could only find a weak association between annual flow extremes and annual population change. This suggests intermediate variations in river flows may have a negligible influence on annual population change or are idiosyncratic in their effect within each waterway or on different life stages. The one population which did not follow this trend occurred in the largest waterway and was subject to legal recreational fishing, suggesting the magnitude of impacts of disturbance on populations occupying larger systems are reduced, and/or that recreational fishing hinders recovery rates following episodic disturbance events such as drought. Our results suggest that forecasting and management of long-lived freshwater fish must incorporate multi-year planning to include factors such as the maintenance of refuges, connectivity and increased protection of mature fish to aid recovery.